Analisis Pendapatan Usahatani Cabai Merah Keriting di Kecamatan Getasan Kabupaten Semarang - Ginting, Namira Widiana; Handayani, Migie; Prasetyo, Edy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Curly red chili is one type of horticultural plant that has relatively high economic value and has a continuously increasing market potential. Curly red chili farmers utilize this situation to optimize their business income. This research aims to analyze the influence of factors such as land area, seed quantity, fertilizer quantity, pesticide quantity, and labor quantity on the income of curly red chili farming. This research was conducted from October to December 2023 in Batur Village, Getasan District, Semarang Regency. The research location was purposively selected considering that Batur Village is one of the largest curly red chili-producing villages in Getasan District. The research method used was a survey method. The data analysis methods used were production cost analysis, revenue, income, profitability, one sample t-test, and multiple linear regression analysis. The research results show that the production cost, revenue, and income of farming on an average land area of 0.2 hectares were IDR 22,954,245/MT, IDR43,502,604/MT, and IDR 20,548,359/MT respectively. The profitability obtained was 117%. Based on the multiple linear regression analysis results, it is shown that land area, seed quantity, fertilizer quantity, pesticide quantity, and labor quantity simultaneously affect the income of curly red chili farming. Land area, seed quantity, and fertilizer quantity have a significant effect on the income of red curly chili farming, while pesticide quantity and labor quantity partially do not affect the income of curly red chili farming. Variables that have a positive effect on income are land area, seed quantity, pesticide quantity, and labor quantity, while fertilizer quantity has a negative effect on the income of curly red chili farming.